Analisis perhitungan harga pokok produksi popcorn menggunakan metode full costing di UKM Tegal Watu - Wanda Zuniati Sukma; Dian Farida Asfan; Abdul Azis jakfar (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Popcorn is a corn-based snack that has a delicious taste. Popcorn is classified as a snack for a diet because popcorn is a cholesterol-free food, high in fiber, dry, and low in sugar. Consequently, consumer interest in popcorn is very high. This research was conducted to calculate the cost of popcorn production using the full costing method and determine the difference between the selling price and a 50% profit. Calculating the cost of production using the full costing method includes all elements of costs and is charged in the calculation of the cost of production. These costs include raw material, labor, and factory overhead costs. There is a price difference between calculating the cost of production and the product selling price using the company method and the full costing method. The cost of production of popcorn using the company method was IDR.2,007.31 per package while using the full costing method, it was IDR.2,248.39 per package. The selling price of the product with a 50% profit using the company method was IDR.3,016.25 per pack, and the full costing method was IDR.3,368.02 per pack. The price difference is due to calculations using the company method that exclude all cost elements in the COGS (Cost of Goods Sold) calculation. While using the full costing method, all costs are charged to the COGS calculation. The difference in the cost of production of the two methods is IDR 351.77. The company use full costing method to give the price for their product.